Capillary rise simulation of saline waters of different concentrations in sandy soils - Natthawit Jitrapinate (KKU Engineering Journal, 2016)
Soil salinity causes corrosion of engineering structures worldwide. The main cause of soil salinization is capillary rise of saline groundwater. Soil salinity can be mitigated once the capillary rise of saline groundwater in soils is understood. The objective of this paper is to present experimental results of capillary rising rates of different salt concentration waters in three sandy soils. Each sample comprised of a soil column 300-mm height and 50-mm in diameter steeped in a 25-mm deep saline water pool for a time period to allow for the capillary action to develop. The salinity strength varied from fresh water, EC = 2 dS/m, to medium saline (50, 100, and 150 dS/m), and to high saline water (200 dS/m). It was found that the highest rate of capillary rise occurred in medium saline waters, while the lowest is the fresh water. The very saline water has lower rate than the medium ones but higher than fresh water.